The Narrative in 2009 (XXI Century. Spanish Literature and Culture)
This work reviews the most noteworthy Spanish novels of 2009. The article offers up a review of each novel, taking into account different thematic and formal aspects. Along with authors of large literary trajectories, readers
Keywords: criticism; novel; reality; fiction; Spanish novel 2009